Strategic impact management of wind power projects - Lima, Fátima (2013)
Wind power projects, despite comparatively to conventional energy sources being considered cleaner alternatives, are not devoid of side effects requiring accurate assessment in order to attain a sustainably managed process. This paper presents a detailed overview of the most pertinent environmental and human effects of wind farms, encompassing Landscape and visual effect; Shadow flicker effect; Electromagnetic interferences; Noise emission; Wildlife; Land occupation and usage; Water resources; Air quality and Carbon footprint; Socio-economic; Architectural or archeological patrimony impact perceptions. Impact management schemes (IMS) are proposed in order to expose strategies to effectively reduce identified negative outcomes, throughout the different phases of implementation of wind power projects. The IMS can give an important contribute to mitigate expected negative impacts and to avoid practices that might adversely influence community’s perception.